Implementación e Impacto de las Buenas Prácticas de Manufactura (BPM) en la Planta Quesera de la Cooperativa Agropecuaria El Salinerito. - Chamorro Chamorro, María Isabel (2017)
The present systematization analyses the processes at the community level and at the dairy plant "El Salinerito", which were carried out, after the Government imposed Good Manufacturing Practices (GMP) compliance, through the Ecuadorian Regulation for Food 3253. In this systematization the results of a hygienic sanitary diagnosis were analysed, and it was verified that if there was compliance with the established actions to obtain the required certification. GMP demands the inspection of facilities, equipment, utensils, personnel, raw material and inputs, production operations, packaging, packaging, labelling, storage, transport and commercialization of the product. In all stages of the process, deficiencies were found, as well as in the design of processes and physical structure of the plant, although they knew all the elements of the correct manufacture, could not apply them in the manufacture of their products, so the facilities presented many risks of contamination in the final product. In the process of delivering raw material, it was even more difficult for producers in the communities surrounding the area due to the high prices that they need to implement all the requirements. The systematization identifies the difficulty of implementing GMP for El Salinerito, despite being a well-known community micro-enterprise, with a long history of producing quality products.